Nutrição com boro na soja em função de doses, modos, épocas de aplicação e disponibilidade de água no solo - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Soya is one of the most demanding annual crops in Boron (B). However, the management of the fertilization with this micronutrient should be carried out with prudence, particularly when related to the doses to be applied, because the appropriate and toxic level are close. A factor that is directly related to the amount of B absorbed by the plants is the availability of water in the soil, the B being transported to the roots by mass flow and root trapping. With the objective of evaluating the plant and production components, productivity and nutrition with boron in the soybean crop as a function of doses, times, mode of application and the availability of water in the soil, were implanted two experiments at the State University of Goiás, UEG Campus Ipameri. In a greenhouse, the experiment was carried out with a Water Retention Capacity (WRC) and boron doses, with a completely randomized experimental design (DIC), in a 3 x 5 factorial arrangement with three soil retention capacities (50, 70, 90% WRC), five doses of boric acid (0, 0.5, 1.0, 1.5 and 2.0 mg dm³) and four repetitions in 5 dm³ vessels, with the variety NS5909. The variables analyzed were fresh mass and shoot dry weight, boron accumulation in the aerial part, boron accumulation in the root, total boron accumulation, number of pods per plant, number of grains per pod, weight of 100 grains and productivity of grains per plant. Another experiment was carried out in the field at the Campus Ipameri experimental farm, with a randomized block design with 9 treatments and 4 replications. The doses were 0.0; 0.5; 1.0; 1.5; 2.0 kg ha-1, spraying on desiccation of weeds before sowing; 0.5 kg ha-1 of B together with the 2-28-18 NPK fertilizer in the sowing furrow; Foliar application with 0.3 kg ha-1, in V4, foliar application with 0.3 kg ha-1 , in R1, foliar application of 0.15 kg ha-1 in V4 plus 0.15 kg ha-1 in R1. The variables analyzed were boron content in leaf and grains, boron accumulation in the plant in the full flowering phase, number of pods per plant, number of grains per pod, weight of 100 grains and productivity. With the low availability of water in the WRC of 50% the plants did not respond to borated fertilization, WRC 70% boron accumulation is increasing, aerial and root dry mass, pod number, number of grains per pod and 100 grain mass increased up to the doses 0.7 and 1.0 mg dm-3 , WRC 90%, the soybean responds linearly to dry shoot, root and boron accumulation. The application of boron in the different doses, times and modes did not influence most agronomic components tested.
Keywords: Glicyne max; adubação boratada; micronutriente; absorção; solo; Glicyne max; borated fertilization; micronutrient; absorption; soil; CIENCIAS AGRARIAS